Application of spectral-domain optical coherence tomography technique to in-process measure hole depth during femtosecond laser drilling in different alloys - P. Xu; Y. Yu; R. J. Liu; K. Zha; L. Zhou; Y. T. Liu; Z. Xu (AIP Advances, 2023)
In this paper, a real-time diagnostic based on the spectral-domain optical coherence technique has been developed to measure the hole depth during femtosecond laser drilling. This diagnostic borrows the idea of a fiber interferometer, and the hole is integrated as a part of the sample arm. By means of investigating the interference fringes detected by the line camera, the hole depth can be extracted. This diagnostic utilizes a broadband small-volume super-luminescent diode as the coherent light source, which has a central wavelength of 833 nm and a full width at half maximum of 24 nm. It has a temporal resolution of 50 µs and a maximal theoretic depth resolution of 12.8 µm. Three kinds of metal samples have been tested, confirming the ability of depth measurement. Copper has been proven to have the best-normalized reflectivity during drilling compared with aluminum alloy and stainless steel.